A non-inverting single-switch buck-boost converter based LED driver - Devi Maheswaran; Sreedevi Vellithiruthi Thazhathu; Deepa Thangavelusamy (Institute of Advanced Engineering and Science, 2023)
This paper focuses on a single-switch buck-boost (SSBB) converter for light emitting diode (LED) lighting applications. The proposed LED driver with power factor correction (PFC) shows enhanced performance in terms of input power factor, efficiency and reduced voltage stress across the switch. The presented LED driver is operated in discontinuous conduction mode (DCM). The input PFC is carried out using average current mode control (ACMC) and the controller is optimized using artificial bee colony (ABC) algorithm. A hardware prototype of 50W LED driver with ACMC for PFC is implemented using a programmable interface circuit (PIC) microcontroller. The experimental results are presented and the performance is compared with a conventional buck boost LED driver. The proposed SSBB LED driver achieves an input power factor of 0.96 with an efficiency of 98%.